Women and the Ballad Trade in Eighteenth-Century England - Atkinson, David (FOCUS: Papers in English Literary and Cultural Studies, 2018)
Knowing that women sold ballads in the eighteenth-century streets it is but a small step to imagining them as characters out of Hogarth’s engravings, impoverished, debased, or defiant. No doubt there is some truth in that characterization, but overall the variety of women’s experiences in the ballad trade was very much broader than this. While a good deal of attention has been paid to the women’s contributions to the eighteenth-century book trade, comments specifically concerning the ballad trade have been fairly superficial, with the exception of Paula McDowell’s studies of some individual women early in the century (cited below). This paper presents some evidence for the different ways in which women were involved with the ballad trade, paying attention to their economic role, and interrogating some contemporary visual and literary representations of ballad women.